ISLAMIZATION AND THE SOCIO-ECONOMIC HISTORY OF JAMBI MALAY - Teguh Adimarta, Saidina Usman, Nori Nopita Sari, (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract One theory of the arrival of Islam to the archipelago states that the arrival of Islam was brought by merchants. There are those who say that the merchants came from Gujarat and some who got direct opinions from Arabia. Not a few also disagree that Islam was brought to the archipelago by traders, but rather by religious scholars from Arabia. This paper is not to discuss the pros and cons of this theory, but focuses on the relationship between trade activities and Islamization in the Jambi remoted area. By using historical research methods covering heuristics, internal and external criticism, interpretation and historiography, this article argues that the process of Islamization in Jambi is similar to the processes and flows of Islamization that occurred in other regions in Sumatra.